Implementations of digital technologies in COVID -19 pandemic and other health threats: multi nationals responses - Pathak, Krishna Prasad (2021)
COVID-19 has created enormous challenges for health systems around the world. An immense range of digital health technologies has been considered as strategies. The aim of this article is to describe the implementation of digital technologies during the COVID-19 pandemic in prevention, diagnosis and treatment globally. Relevant articles published electronically in English using the following terms "COVID-19", "2019-nCov", "coronavirus", terminologies, "severe acute respiratory syndrome 2", SARS-CoV-2", "access to digital health, telemedicine and e-health, challenges and opportunities, in different data sources were researched. A total of 455 articles were found, and 46 published articles about prevention, treatment, and diagnosis approaches were selected. Digital technologies were useful in holistic control, care management and prevention, digital information, data collection, transfer and storage, frontline protection, risk reduction, analysis and adequate system of monitoring information during the pandemic situation, applying teleservice, consultations to specialists via online/offline, intelligent health system, which decreased the burden of patients to health professionals in institutions. In addition, it helped provide safe, rapidly and adequate patient data; and to avoid contamination for healthcare providers, the general population and patients. Still, the use of digital technologies in health is insufficient in many countries. It is essential to expand alternative ways of adapting digital technologies in health practices, but also to implement other studies on the use of digital health technologies beyond the focus on COVID-19.